Evaluation of rice genotypes for resistance to the stalk-eyed fly (Diopsis longicornis) in rice in Uganda - Ganteh Weelar, Charles; Otim, Michael Hilary; Lamo, Jimmy; Awio, Bruno; Ochwo-Ssemakula, Mildred (International Journal of Agronomy and Agricultural Research (IJAAR), 2016)
Globally, rice production is limited by abiotic and biotic factors. Of the insect pests attacking rice, the stalk-eyed fly is the most abundant. Major rice growing districts in Uganda are affected, and varieties grown by farmers are susceptible. The objective of this study was to identify sources of resistance to stalk-eyed flies among improved rice genotypes in Uganda. Fifty genotypes from the Africa Rice Centre, IRRI, South Korea and the National Crops Resources Research Institute (NaCRRI) in Uganda were screened under cage and field conditions at NaCRRI. Trials were laid out in an alpha lattice design, with 3 replications, for both experiments. Natural infestation (D. longicornis or D. apicalis) was used in the field while cage trials utilized artificial infestation with D. longicornis. Data on deadhearts were collected from seedling to tillering stages, at 7, 14, 21 and 28 days. Analyses of variance were performed using restricted maximum likelihood. Infestation levels for 31 (62%) rice genotypes were the same under both field and cage conditions, 4 (8%) genotypes showed higher susceptibility in the cage than in the field and 15 (30%) were more resistant in the cage than in the field. Genotypes NERICA 4, TXD306, NM7-22-11- B-P-1-1 and K85 were identified as the most resistant varieties. F3 genotypes (GSR IR1- 5-S14-S2-Y1 x K85, Gigante x NERICA4, NERICA4 x Gigante, NERICA1x NERICA4, NERICA4 x NERICA6, and NERICA4 x SUPA) were also found resistant. These genotypes were recommended for release and further advancement, respectively.
Keywords: Improved rice genotypes; Stem borers; Infestations; Deadhearts